Towards a Blockchain-based Architecture for Data Provenance Management in the Internet of Things - Vieira, Marcos Alves; Carvalho, Sergio T. (Workshop em Blockchain: Teoria, Tecnologias e Aplicações (WBlockchain); 2021: Anais do IV Workshop em Blockchain: Teoria, Tecnologias e AplicaçõesDO - 10.5753/wblockchain.2021.17132, 2021)
An Internet of Things (IoT) scenario is a heterogeneous and complex environment, where large volumes of data are constantly generated, manipulated, and transferred between different devices. In this context, some difficulties may arise, such as the correct identification of the devices generating the data, the trustworthiness of these devices and their generated data, detecting abnormal behavior, and controlling access to the data. Data provenance allows maintaining information about the origin of the data, the operations through which this data has undergone, and its processing history, from its creation to its current state. Aiming to provide means to mitigate the mentioned problems, we propose an architecture for data provenance management in IoT environments, enabling different levels of granularity, using a distributed ledger architecture.